2000
DOI: 10.1128/jcm.38.2.818-825.2000
|View full text |Cite
|
Sign up to set email alerts
|

Specific and Rapid Detection by Fluorescent In Situ Hybridization of Bacteria in Clinical Samples Obtained from Cystic Fibrosis Patients

Abstract: We report on the rapid and specific detection of bacteria commonly isolated from clinical specimens from cystic fibrosis (CF) patients by fluorescent in situ hybridization (FISH). On the basis of comparative sequence analysis, we designed oligonucleotide probes complementary to species-specific 16S rRNA regions of these microorganisms and demonstrated the specificities of the probes by hybridization of different remotely related as well as closely related reference strains. Furthermore, in a pilot project we i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
89
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(91 citation statements)
references
References 23 publications
1
89
0
1
Order By: Relevance
“…The FISH probe 5 0 -/5ATTO633N/TGC CAC CCG TAG GTG T-3 0 (Brown et al, 2015) was used to detect Candidatus Xiphinematobacter rivesi (in green), and the FISH probe Burkho_1 5 0 -5ATTO550/RCC CTC TGT ACC GAC CAT-3 0 was designed to target the 16S rRNA of our Burkholderiaceae endosymbiont (in red) in Xiphinema nematodes was based on the probe Burkho designed for Burkholderia spp. (Hogardt et al 2000). After hybridization, specimens were washed twice at 46°C for 30 min in 1 mL of prewarmed hybridization wash buffer (20 mM Tris-HCl, 0.02% wt/vol SDS, 0.008 M NaCl, 5 mM EDTA).…”
Section: Fluorescence In Situ Hybridization (Fish) and Confocal Lasermentioning
confidence: 99%
“…The FISH probe 5 0 -/5ATTO633N/TGC CAC CCG TAG GTG T-3 0 (Brown et al, 2015) was used to detect Candidatus Xiphinematobacter rivesi (in green), and the FISH probe Burkho_1 5 0 -5ATTO550/RCC CTC TGT ACC GAC CAT-3 0 was designed to target the 16S rRNA of our Burkholderiaceae endosymbiont (in red) in Xiphinema nematodes was based on the probe Burkho designed for Burkholderia spp. (Hogardt et al 2000). After hybridization, specimens were washed twice at 46°C for 30 min in 1 mL of prewarmed hybridization wash buffer (20 mM Tris-HCl, 0.02% wt/vol SDS, 0.008 M NaCl, 5 mM EDTA).…”
Section: Fluorescence In Situ Hybridization (Fish) and Confocal Lasermentioning
confidence: 99%
“…This study is subject to a limitation of the minimum detection limit (FISH 10 3 microorganisms ml )1 vs. 10 5 microorganisms ml )1 for Gram stain). 6 Only the samples that showed yeast by Gram staining were evaluated by a follow-up FISH assay. Some specimens with a low number of yeast cells could be missed when performing the Gram stain screening process, which would affect the sensitivity analysis of the FISH assay in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, fluorescent in situ hybridisation (FISH) of whole cells with a fluorescently-labelled, 18S rRNAtargeted, oligonucleotide probe has been used for the sensitive detection of microorganisms. [3][4][5][6] Several authors have reported the identification of Candida species from blood cultures using FISH, 7-9 but only a few studies have investigated the identification of Candida species in other types of clinical samples. 10,11 In this study, we developed a modified FISH protocol for differentiation of C. albicans from non-C. albicans species in clinical specimens without culturing (except for blood cultures), evaluated the sensitivity and specificity of this protocol compared with traditional identification methods, and described the protocol detail for the application of the FISH protocol on blood culture, bronchoalveolar lavage (BAL) fluid, abscess ⁄ puncture liquid and urine samples.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence in situ hybridization (FISH) is a rapid diagnostic staining procedure based on the specific binding of fluorescently labelled probes to ribosomal target RNA. It has been broadly evaluated for the identification of various microorganisms in clinical samples by fluorescence microscopy (Hogardt et al 2000;Kempf et al 2000;Poppert et al 2002;Poppert et al 2005Poppert et al , 2010aWellinghausen et al 2005). FISH-based differentiation of pathogens is even possible from more difficult specimens such as blood culture materials (Hogardt et al 2000;Kempf et al 2000;Poppert et al 2010a,b) or formalinfixed, paraffin-embedded tissue samples (Rü ssmann et al 2003;Yilmaz et al 2007;Hagen et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…We developed and evaluated a rapid FISH-based microscopic screening procedure for Leishmania spp. in tissue samples under standard conditions (Hogardt et al 2000;Kempf et al 2000) as a useful tool for endemic areas and travel medicine clinics. It is based upon newly designed probes to optimize screening and to facilitate diagnosis.…”
Section: Introductionmentioning
confidence: 99%